Detergent-Resistant, Ceramide-Enriched Domains in Sphingomyelin/Ceramide Bilayers - Sot, Jesús (Biophysical Society, 2006)
When cell membranes are treated with Triton X-100 or other detergents at 4°C, a nonsolubilized fraction can often be recovered, the “detergent-resistant membranes”, that is not found when detergent treatment takes place at 37°C. Detergent-resistant membranes may be related in some cases to membrane “rafts”. However, several basic aspects of the formation of detergent-resistant membranes are poorly understood. To answer some of the relevant questions, a simple bilayer composition that would mimic detergent-resistant membranes was required. The screening of multiple lipid compositions has shown that the binary mixture egg sphingomyelin/egg ceramide (SM/Cer) exhibits the required detergent resistance. In detergent-free membranes composed of different mixtures of SM and Cer (5–30 mol % of Cer) differential scanning calorimetry, fluorescence spectroscopy, and fluorescence microscopy experiments reveal the presence of discrete, Cer-enriched gel domains in a broad temperature range. In particular, at temperatures below SM phase transition (≈ 40°C) two gel (respectively Cer-rich and SM-rich) phases are directly observed using fluorescence microscopy. Although pure SM membranes are fully solubilized by Triton X-100 at room temperature, 5 mol % Cer is also enough to induce detergent resistance, even with a large detergent excess and lengthy equilibration times. Short-chain Cers do not give rise to detergent resistance. SM/Cer mixtures containing up to 30 mol % Cer become fully soluble at ∼50°C, i.e., well above the gel-fluid transition temperature of SM. The combined results of temperature-dependent solubilization and differential scanning calorimetry reveal that SM-rich domains are preferentially solubilized over the Cer-rich ones as soon as the former melt (i.e., at ∼40°C). As a consequence, at temperatures allowing only partial solubilization, the nonsolubilized residue is enriched in Cer with respect to the original bilayer composition. Fluorescence microscopy of giant unilamellar vesicles at room temperature clearly shows that SM-rich domains are preferentially solubilized over the Cer-rich ones and that the latter become more rigid and extensive as a consequence of the detergent effects. These observations may be relevant to the phenomena of sphingomyelinase-dependent signaling, generation of “raft platforms”, and detergent-resistant cell membranes.